Biphasic regulation of RNA interference during rotavirus infection by modulation of Argonaute2. (26th August 2019) - Mukhopadhyay, Urbi; Chanda, Shampa; Patra, Upayan; Mukherjee, Anupam; Komoto, Satoshi; Chawla‐Sarkar, Mamta
Abstract: RNA interference (RNAi) is an evolutionary ancient innate immune response in plants, nematodes, and arthropods providing natural protection against viral infection. Viruses have also gained counter‐defensive measures by producing virulence determinants called viral‐suppressors‐of‐RNAi (VSRs). Interestingly, in spite of dominance of interferon‐based immunity over RNAi in somatic cells of higher vertebrates, recent reports are accumulating in favour of retention of the antiviral nature of RNAi in mammalian cells. The present study focuses on the modulation of intracellular RNAi during infection with rotavirus (RV), an enteric virus with double‐stranded RNA genome. Intriguingly, a time point‐dependent bimodal regulation of RNAi was observed in RV‐infected cells, where short interfering RNA (siRNA)‐based RNAi was rendered non‐functional during early hours of infection only to be reinstated fully beyond that early infection stage. Subsequent investigations revealed RV nonstructural protein 1 to serve as a putative VSR by associating with and triggering degradation of Argonaute2 (AGO2), the prime effector of siRNA‐mediated RNAi, via ubiquitin–proteasome pathway. The proviral significance of AGO2 degradation was further confirmed when ectopic overexpression of AGO2 significantly reduced RV infection. Cumulatively, the current study presents a unique modulation of host RNAi during RV infection, highlighting the importance of antiviral RNAi in mammalian cells.